TEORI PEDAGOGIK PENDIDIKAN MAHMUD YUNUS - Indah Muliati; Rini Rahman (Islam Transformatif : Journal of Islamic Studies, 2019)
This research is library research, which makes books as the main data source.  This research focuses on a pedagogical theory developed by Mahmud Yunus. From a variety of searches can be put forward several Pedagogic Theories developed by Mahmud Yunus namely;  1) The purpose of education according to Mahmud Yunus is to prepare students so that when they become adults they will be able and capable of doing the work of the world and the practice of the hereafter so as to create happiness with the world and the hereafter.  2) Mahmud Yunus implements the halaqah and classical teaching system in Madras School, which was developed by Mahmud Yunus is a classical system.  3) Mahmud Yunus in teaching using the lecture method, question and answer (dialogue), assignments, demonstrations, group work and uswatun hasanah (exemplary).  4) In teaching Arabic the Mahmud Yunus uses the direct method.  5) In teaching, he uses various approaches namely rational, emotional, and practical approaches.  6) Mahmud Yunus is a figure who pioneered an integrated curriculum in Islamic educational institutions.  7) If you want to improve education and teaching in Indonesia it is important to improve teachers by preparing teachers in teacher schools.